2013
DOI: 10.1302/0301-620x.95b1.29835
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the cost-effectiveness of total hip and knee replacement

Abstract: The aim of this study was to perform a cost-utility analysis of total hip (THR) and knee replacement (TKR). Arthritis is a disabling condition that leads to long-term deterioration in quality of life. Total joint replacement, despite being one of the greatest advances in medicine of the modern era, has recently come under scrutiny. The National Health Service (NHS) has competing demands, and resource allocation is challenging in times of economic restraint. Patients who underwent THR (n = 348) or TKR (n = 323)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
228
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(248 citation statements)
references
References 25 publications
8
228
1
1
Order By: Relevance
“…Using these tariffs a recent report found an average cost per QALY gained to be £5,623 for the first five years after surgery [14]. Another study analysed the cost per QALY for the life expectancy of their patient cohort and demonstrated a cost per QALY of £4,704, accounting for deterioration in outcome with time and potential revision of the costs [2]. There is consensus then that the cost per QALY for knee arthroplasty is far below the value of £20,000 suggested by the UK national institute for clinical excellence as the threshold by which interventions are deemed cost effective [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using these tariffs a recent report found an average cost per QALY gained to be £5,623 for the first five years after surgery [14]. Another study analysed the cost per QALY for the life expectancy of their patient cohort and demonstrated a cost per QALY of £4,704, accounting for deterioration in outcome with time and potential revision of the costs [2]. There is consensus then that the cost per QALY for knee arthroplasty is far below the value of £20,000 suggested by the UK national institute for clinical excellence as the threshold by which interventions are deemed cost effective [15].…”
Section: Discussionmentioning
confidence: 99%
“…This methodology assumes static health after oneyear and no need for further intervention, which is considered the undiscounted health gain [8]. The QALYs gain was discounted at a rate of 5 % for each year of life expectancy to reflect a diminishing gain with time [9], as has been previously employed in arthroplasty health economic analysis [2]. The cost per QALY was then calculated (QALY gained/cost of prosthesis) at one year and for the expected lifetime of the cohort (adjusted and unadjusted).…”
Section: Study Population and Trial Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Total hip arthroplasty (THA) is one of the most commonly performed and cost-effective orthopedic procedures [1,2]. By 2030, the number of primary THA in the United States is estimated to rise by 174% to 572,000 procedures [3].…”
mentioning
confidence: 99%